DEVELOPMENT OF ENGLISH LANGUAGE COURSES TO PREPARE PRIMARY SCHOOL STUDENTS FOR PARTICIPATION IN INTERNATIONAL QUALITY ASSESSMENT PROGRAMS - Turgunova Iroda Tolibjonovna, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The globalization of education and the increasing role of English as an international language necessitate the development of scientifically grounded language courses for primary school students. This study explores the principles and methodologies essential for designing English language courses that effectively prepare young learners for participation in international quality assessment programs such as PIRLS, TOEFL Primary, and Cambridge English Young Learners. Drawing upon theories of second language acquisition (SLA), cognitive development, and communicative language teaching (CLT), the research emphasizes the importance of integrating Content and Language Integrated Learning (CLIL), digital tools, and multimodal teaching strategies. The study highlights the role of formative and summative assessments aligned with the Common European Framework of Reference for Languages (CEFR) and underscores the necessity of teacher training and parental involvement in optimizing language learning outcomes. The findings suggest that a structured, research-based approach to English language instruction enhances students‟ linguistic proficiency, test readiness, and long-term academic success. Future research should focus on longitudinal studies to assess the sustained impact of these instructional methods.